Nuclear Weapons and the Environment : an ecological case for non-proliferation - Perry, John, 1946 February 7- (Lanham: Lexington Books, 2021)
"In Nuclear Weapons and the Environment, John Perry highlights the grave risks associated with the continued proliferation of nuclear weapons, pointing not just to the dangers to human life but to the severe environmental damage caused by nuclear device testing"--
Introduction to book on non-proliferation -- Historical background -- The nuclear non-proliferation treaty -- The risk of a regional nuclear war between India and Pakistan -- The environmental and human cost of producing nuclear weapons -- Chernobyl : the world's worst nuclear accident -- The greatest industrial accident in history / Fukushima Daiichi -- The greatest deproliferation of nuclear weapons in the postwar period -- Nuclear proliferation through theft, terrorism or neglect -- Nuclear weapons testing : inflicting the conditions of nuclear war on fragile environments -- Pakistan : the biggest and most important exporter of nuclear technology in the history of the nuclear age -- The ultimate weapon as the ultimate guarantee of regime survival : North Korea and the bomb -- Conclusion.
Includes bibliographical references (pages 163-175) and index.
Keywords: Nuclear weapons -- Environmental aspects; Nuclear weapons -- Testing -- Environmental aspects; Nuclear energy -- Environmental aspects; Nuclear nonproliferation